Chronic alcohol abuse may lead to high skin iron content, but not to hepatic siderosis - Paulke, Alexander; Skopp, Gisela (Forensic science international, 2019)
Introduction - In forensic cases, ante mortem chronic alcohol abuse can be of central importance in clarifying circumstances of death. However, reliable markers of alcohol consumption, which are still available postmortem, are needed. In addition to medical history data which may not be always authentic, the determination of ethyl glucuronide (EtG) in hair as a promising parameter is of no value in cases of missing or cosmetically treated hair. On the other hand, there exist reports that iron ions accumulate in liver tissue (siderosis) during chronic, excessive alcohol consumption, which, therefore, may be useful to serve as alcohol abuse correlate. However, the influence of ethanol on iron stored in the liver has not been adequately investigated and the study situation appears to be inconsistent. - Aims - The aim of the present study was to assess the suitability of assaying iron concentrations in liver and other tissues as postmortem alcoholism marker. - Methods - The iron concentration in tissue samples (liver, brain, skin, pancreas, spleen), vitreous fluid and blood taken during autopsy was analyzed by atomic absorption spectroscopy. The analytical method has been validated before. Cases were divided into two groups: chronic alcohol abusers and non-chronic alcohol consumers including total abstainers using ethyl glucuronide levels in hair as well as anamnestic data as criteria. - Results - No elevated iron concentrations in the liver of chronic alcohol abusers were detected. Surprisingly, the iron concentration in skin tissue was found to be significantly higher in cases of chronic alcohol abuse, independent on whether fatty liver or liver cirrhosis was present (as diagnosedduring autopsy). In 18.5% of the cases, chronic alcohol abuse was not confirmed by the EtG concentration in hair. Thus, anamnestic data should not be overestimated. - Conclusion - The general assumption that chronic alcohol abuse induces hepatic siderosis, i.e. high iron concentrations in liver tissue, has not been supported by results of the present study. However, there seems to exist a correlation between chronic alcohol abuse and high iron concentrations in the skin.
Gesehen am 30.01.2020